Aerospace series. Steel X5CrNiCu 17-4 (1.4542). Air melted. Solution treated and precipitation treated. Plates. 6 mm ≤ a ≤ 100 mm. Rm ≥ 1 070 MPa. (17th January 2023) - British Standards Institution,
No abstract available